(untitled) (Revista Sistemas de Producción Agroecológicos, 2017)
Homotoxicological medicine combines homeopathy with conventional methods of veterinary practice for the benefit of the patient, supported by internal medicine, uses several recognized techniques such as ultrasound, radiology and hematology, among others, to obtain an adequate diagnosis. Under this discipline it is considered that the disease is caused by homotoxins, which are those factors that alter the health of the animal, but do not act the same in all animal species and races. The mechanism of action of homotoxicological drugs is based on the immunological assistance reaction, which stimulates and modulates defense mechanisms and natural organic reactions, through the biochemical restructuring of tissues; compared with allopathic medicine. It is so the homotoxicology has changed the approach of the therapeutic plan, seeking to stimulate the body so that naturally, through inflammatory processes, and excretion, among others, eliminate the homotoxins, without suppressing the clinical signs that are the body’s response to combat them. This article compiles the use of homotoxicology as an alternative therapy in the treatment of gastrointestinal system disorders in canines and felines, such as periodontal disease, megaesophagus, gastritis, dilatation/acute gastric volvulus, enteritis, colitis, impermeable bowel syndrome, megacolon, chronic active hepatitis, cholangiohepatitis, liver cirrhosis, acute and chronic pancreatitis and surgical procedures such as dental extraction.